PIEZO2 is required for mechanotransduction in human stem cell-derived touch receptors - Schrenk-Siemens, Katrin; Wende, Hagen; Prato, Vincenzo; Song, Kun; Rostock, Charlotte; Utikal, Jochen; Lechner, Stefan; Siemens, Jan (Nature neuroscience, 2015)
Human sensory neurons are inaccessible for functional examination, and thus little is known about the mechanisms mediating touch sensation in humans. Here we demonstrate that the mechanosensitivity of human embryonic stem (hES) cell-derived touch receptors depends on PIEZO2. To recapitulate sensory neuron development in vitro, we established a multistep differentiation protocol and generated sensory neurons via the intermediate production of neural crest cells derived from hES cells or human induced pluripotent stem (hiPS) cells. The generated neurons express a distinct set of touch receptor-specific genes and convert mechanical stimuli into electrical signals, their most salient characteristic in vivo. Strikingly, mechanosensitivity is lost after CRISPR/Cas9-mediated PIEZO2 gene deletion. Our work establishes a model system that resembles human touch receptors, which may facilitate mechanistic analysis of other sensory subtypes and provide insight into developmental programs underlying sensory neuron diversity.